2022
DOI: 10.1007/s00376-022-1360-7
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in Simulated Ocean Net Surface Heat Fluxes over the North Atlantic

Abstract: The change in ocean net surface heat flux plays an important role in the climate system. It is closely related to the ocean heat content change and ocean heat transport, particularly over the North Atlantic, where the ocean loses heat to the atmosphere, affecting the AMOC (Atlantic Meridional Overturning Circulation) variability and hence the global climate. However, the difference between simulated surface heat fluxes is still large due to poorly represented dynamical processes involving multiscale interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 108 publications
0
3
1
Order By: Relevance
“…2c). This is in contrast to previous studies, which have attributed the widespread underestimation of subtropical MHT in numerical models (e.g., Liu et al, 2022) to the overly diffusive thermocline simulated in z-coordinates (Msadek et al, 2013;Roberts et al, 2020), which results in a warmer than observed AMOC lower limb.…”
Section: Lagrangian Particle Trackingcontrasting
confidence: 99%
“…2c). This is in contrast to previous studies, which have attributed the widespread underestimation of subtropical MHT in numerical models (e.g., Liu et al, 2022) to the overly diffusive thermocline simulated in z-coordinates (Msadek et al, 2013;Roberts et al, 2020), which results in a warmer than observed AMOC lower limb.…”
Section: Lagrangian Particle Trackingcontrasting
confidence: 99%
“…The ENSO signal has profound influences on the precipitations in China and its surrounding areas (Liu et al, 2022;Gao and Li, 2023), and the leading signal of the OHT in the WPWP to ENSO may play a role in the precipitation forecast over this region.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, models have tended to underestimate the MHT at latitudes near 26° N in the Atlantic, even if producing realistic estimates of the AMOC strength. For example, Liu et al [ 80 ] recently showed that nearly all AMIP6 models (Atmospheric Model Intercomparison Project Phase 6; [ 81 ]) underestimated the MHT at 26° N, with the ensemble mean of all models over the period from 1985 to 2015 showing a mean MHT about 0.3 PW lower than the 1.2 PW estimate from RAPID. A similar bias is found in coupled models, where a large ensemble of models from CMIP6 were shown to underestimate the MHT by about 0.2 PW relative to the RAPID MHT estimate [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the commonly used air–sea heat flux datasets (NOC, NCEP, ERA5, JRA-55, MERRA-2, CERES + OAFlux) also underestimate the MHT at 26° N, some of them quite considerably, due to too-weak surface heat losses over the North Atlantic [ 69 , 80 ]. Recent estimates using ‘residual' methods (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation